What does a threatened saproxylic beetle look like? Modelling extinction risk using a new morphological trait database. Issue 8 (1st June 2021) - Hagge, Jonas; Müller, Jörg; Birkemoe, Tone; Buse, Jörn; Christensen, Rune Haubo Bojesen; Gossner, Martin M.; Gruppe, Axel; Heibl, Christoph; Jarzabek‐Müller, Andrea; Seibold, Sebastian; Siitonen, Juha; Soutinho, João Gonçalo; et al.
Abstract: The extinction of species is a non‐random process, and understanding why some species are more likely to go extinct than others is critical for conservation efforts. Functional trait‐based approaches offer a promising tool to achieve this goal. In forests, deadwood‐dependent (saproxylic) beetles comprise a major part of threatened species, but analyses of their extinction risk have been hindered by the availability of suitable morphological traits. To better understand the mechanisms underlying extinction in insects, we investigated the relationships between morphological features and the extinction risk of saproxylic beetles. Specifically, we hypothesised that species darker in colour, with a larger and rounder body, a lower mobility, lower sensory perception and more robust mandibles are at higher risk. We first developed a protocol for morphological trait measurements and present a database of 37 traits for 1, 157 European saproxylic beetle species. Based on 13 selected, independent traits characterising aspects of colour, body shape, locomotion, sensory perception and foraging, we used a proportional‐odds multiple linear mixed‐effects model to model the German Red List categories of 744 species as an ordinal index of extinction risk. Six out of 13 traits correlated significantly with extinction risk. Larger species as well as species with a broad and round body had a higher extinction risk than small, slim and flattened species. Species with short wings had a higher extinction risk than those with long wings. On the contrary, extinction risk increased with decreasing wing load and with higher mandibular aspect ratio (shorter and more robust mandibles). Our study provides new insights into how morphological traits, beyond the widely used body size, determine the extinction risk of saproxylic beetles. Moreover, our approach shows that the morphological characteristics of beetles can be comprehensively represented by a selection of 13 traits. We recommend them as a starting point for functional analyses in the rapidly growing field of ecological and conservation studies of deadwood. Abstract : The extinction risk of saproxylic beetles in Central Europe is not a random process. Species with morphological traits linked to forest structures and deadwood features that have been suppressed or removed by forestry in the last centuries have a higher extinction risk. Abstrakt: Das Aussterben von Arten ist kein zufälliger Prozess und ein Verständnis, warum bestimmte Arten eine höhere Wahrscheinlichkeit haben auszusterben als andere, ist von zentraler Bedeutung für den Naturschutz. Analysen funktionaler Eigenschaften von Arten stellen hierbei einen vielversprechenden Ansatz dar. Viele der an Totholz gebundenen Käferarten sind gefährdet, aber entsprechende Analysen zur Gefährdungssituation der Arten waren bisher durch die fehlende Verfügbarkeit geeigneter morphologischer Eigenschaften limitiert. Um die Mechanismen des Aussterbens von Insekten besser zu verstehen, haben wir den Zusammenhang zwischen morphologischen Eigenschaften und der Gefährdung von Totholzkäfern untersucht. Dabei testeten wir die Hypothesen, ob Arten mit einer dunklen Farbe, mit einem großen und runden Körper, mit geringer Mobilität, mit geringer sensorischer Wahrnehmung und mit robusten Mandibeln besonders stark gefährdet sind. In einem ersten Schritt entwickelten wir ein Messprotokoll für 37 morphologische Eigenschaften und erstellten eine Datenbank für 1, 157 europäische Totholzkäfer. Für 13 ausgewählte und unabhängige morphologische Messwerte für Farbe, Körperform, Fortbewegung, Sinneswahrnehmung und Nahrungssuche von Totholzkäfern berechneten wir mit Hilfe eines gemischten ordinalen Modells den Einfluss auf die Gefährdungskategorie der Deutschen Roten Liste für 744 Totholzkäfer. Sechs der 13 morphologischen Eigenschaften hatten einen signifikanten Einfluss auf die Gefährdungssituation. Große Arten und Arten mit einem breiten und runden Körper waren stärker gefährdet als kleine, schmale und flache Arten. Arten mit kurzen Flügeln waren gefährdeter als die mit langen Flügeln. Im Gegensatz dazu waren Arten mit geringer Flügellast (Masse pro Flügelfläche) und großem Mandibel‐Seitenverhältnis (kürzer und robustere Mandibeln) stärker gefährdet. Unsere Studie liefert neue Evidenz inwieweit morphologische Eigenschaften, über die bereits intensiv betrachtete Körpergröße hinaus, die Gefährdungssituation von Totholzkäfern beeinflussen. Des Weiteren zeigt unser Ansatz, dass die Morphologie von Käfern umfassend durch 13 selektierte Messgrößen beschrieben werden kann. Wir schlagen diese als Ausgangspunkt für weitere funktionelle Analysen in dem sich rasch entwickelnden Forschungsfeld ökologischer und naturschutzfachlicher Studien zum Thema Totholz vor.